Comprehension processes and outcomes with refutation and expository texts and their contribution to learning. (February 2016) - Diakidoy, Irene-Anna N.; Mouskounti, Thalia; Fella, Argyro; Ioannides, Christos
Abstract: The study compared the comprehension processes and outcomes obtained with refutation and expository text and their association with learning outcomes. After a knowledge pretest, undergraduate students read an extended expository text or a corresponding refutation text that addressed three potential misconceptions about the scientific concept of energy. Think-aloud, cued recall, and posttest data indicated that the positive impact of refutation text was more associated with comprehension outcomes than processes. Refutation text did not influence comprehension processes but facilitated valid inference generation in recall and minimized the negative effects of distortions on learning. The findings suggest the timing of the refutation text effect to be later, after reading, and its nature to be that of neutralizing the influence of any misconceptions on learning from text instead of changing them. Highlights: Memory-associated processes, like paraphrasing, and inferencing during reading contributed to subsequent text recall. Recall was the only contributor to inference generation after reading. Inferences after reading contributed to overall learning from text. Refutation text was positively associated with inferences after reading only. Refutation text minimized the negative impact of distortions on subsequent learning.